PTU-097 Nutritional Screening in Patients with Colorectal Cancer Prior to Elective Surgery: Is it Done Accurately and Does It Predict Outcome?. (17th August 2016) - Wesley, E; Thompson, B; Tham, J; Smart, N; Engel, B; Daniels, I
Abstract : Introduction: Patients undergoing surgery for colorectal cancer (CRC) are at high risk of malnutrition, this is detrimental to their post-operative outcome. Nutritional screening is performed pre-operatively using the malnutrition universal screening tool (MUST) but the accuracy of completion and its ability to predict post-operative outcome is currently unknown. Aims: To assess the frequency and accuracy in which MUST scoring is completed in the real world setting of a colorectal unit of busy teaching hospital To identify whether the pre-operative MUST score predicts poor outcome after CRC surgery in terms of increased risk of complications and length of hospital stay. Methods: 136 consecutive patients undergoing elective surgery for CRC were prospectively independently MUST scored by 2 study investigators. Data was prospectively collected on the MUST score calculated by nursing staff as well as information on patient demographics, operative details and post-operative outcomes. Results: 76 (56%) were male. The age range was 46–97, median 73, 75% of the patients were >65. The BMI range was 14.6–43, median 26.1. 32% of the patients had right colon lesions, 21% left colon and 43% rectal. MUST scoring was almost universally completed by nursing staff (98.5%)but the accuracy was poor with significant differences in scores (p = 0.001). The weight loss component of the scoring was the source of error. 73% of the patients had a MUST score of 0, 19% had a score of 1 and 8% ≥ 2. 60% of patients had their surgery by the laparoscopic approach. 61.5% experienced no post-operative complications, 9.5% experienced significant complications (Clavien-Dindo 3 a-5). Hospital length of stay ranged from 0–43 days, median 6 days. MUST score was not able to predict the risk of post-operative outcome as defined by an increased risk of post-operative complications (p = 0.96) or increased length of hospital stay (p = 0.95). ASA status showed a trend towards significance for predicting post-operative complications (p = 0.06). Conclusion: MUST screening is almost universally done however the accuracy is poor. There is a risk that patients who are at risk of malnutrition and may benefit from nutritional support are being overlooked. MUST screening alone did not predict an increased length of hospital stay or risk of post-operative complications. The prevalence of malnutrition as detected by MUST score was low. This is likely to be because a significant proportion of the patients were overweight or obese. An alternative screening tool such as the short nutritional assessment questionnaire (SNAQ) might be more suitable in this patient group. Disclosure of Interest: None Declared